Case report: Modified transplantation for pediatric patients with pyruvate kinase deficiency - Pang, Yuhui; Qi, Xiaoyu; Qin, Jiayue; Zhai, Xiaoran; Wang, Rongxiao; Cao, Jianzhu; Zhang, Na; Liu, Jinxia; Li, Jianying; Wu, Weihai; Wei, Shanshan; Zhang, Jingjing; et al. (Frontiers in Immunology, 2024)
Pyruvate kinase deficiency (PKD) is an autosomal recessive genetic disease caused by mutations in the PKLR gene. To date, the clinical manifestations of PKD are heterogeneous, ranging from fetal anemia, neonatal jaundice, and severe chronic hemolytic anemia to fully compensated hemolytic anemia. Successful cases of allogeneic hematopoietic stem cell transplantation (allo-HSCT) for PKD have been reported, however, the number of cases is very small, and experiences are very limited. Here, we report two successful cases involving our modified conditioning regimen. This approach is suitable for patients with severe transfusion dependence. In conclusion, for PKD patients with severe transfusion dependence, allo-HSCT is an option and is currently a safe and effective way to completely eliminate the need for transfusions of drugs, such as Mitapivat, or genetic therapies and allow the patient to return to normal life.